Study and Design of a Small Germinated Brown Rice Machine for Home - ปานสาคร สุนัน; สุขนาค ศราวุฒิ; พงษ์ศักดิ์ เบญจวรรณ; สนรัมย์ สุกานดา (Frontiers in Engineering Innovation Research, 2010)
Germinated brown rice product is rich in nutrients and it has gained a great deal of attention. Recently, the low quality of germinated brown rice product (GRB) was found, which cause lack in controlling process. Besides to consume fresh of GRB gave higher of nutrients than dry of GRB product. Thus resulting in higher qualities of GRB, the aim of this study was to design and construct of a small GRB machine for home. In addition, the optimum process of GRB was also investigated base on the physicochemical properties of GRB product. The capacity of GRB machine was 8-9 kg/day and the cubic size 40x60x40 cm. consisted of bucket, time controller, spray unit, baskets sample and solenoid valves for controlling water on-off. At room temperature condition (27 [plusmn] 2 degree Celsius 60 [plusmn] 5%RH) resulted in good physicochemical properties when soaked brown rice in water for 4 hr combined with incubate process at the same condition for 20 hr. During the incubation process, water was sprayed every 4 hr interval which showed lowest in growth microorganism, whilst there was 4 times greater for GABA content compared with brown rice. At this condition was observed in good quality of GRB after cooking such as good flavor and soft of texture.